Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2021
DOI: 10.1002/ece3.7791
|View full text |Cite
|
Sign up to set email alerts
|

Variation in heteroploid reproduction and gene flow across a polyploid complex: One size does not fit all

Abstract: Whole‐genome duplication is considered an important speciation mechanism in plants. However, its effect on reproductive isolation between higher cytotypes is not well understood. We used backcrosses between different ploidy levels and surveys of mixed‐ploidy contact zones to determine how reproductive barriers differed with cytotype across a polyploid complex. We backcrossed F1 hybrids derived from 2X‐4X and 4X‐6X crosses in the Campanula rotundifolia autopolyploid complex, measured backcross fitness, and esti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 54 publications
0
3
0
Order By: Relevance
“…In some cases, triploid offspring can produce functional gametes ( Krahulcová and Krahulec 2000 ) that can result in tetraploid offspring ( Peckert and Chrtek 2006 ), but in others there may be complete reproductive isolation between diploids and tetraploids (i.e., triploid-block, Marks 1966 ). In instances where there is a triploid-block but higher level ploidies in the complex exist, gene flow across ploidies can occur between other intermediates (e.g., pentaploids, Peskoller et al 2021 ; Sutherland and Galloway 2021 ). Despite strong evidence of gene flow across ploidies in some animals ( Bogart et al 2020 ; Novikova et al 2020 ), these processes are even further understudied.…”
Section: Introductionmentioning
confidence: 99%
“…In some cases, triploid offspring can produce functional gametes ( Krahulcová and Krahulec 2000 ) that can result in tetraploid offspring ( Peckert and Chrtek 2006 ), but in others there may be complete reproductive isolation between diploids and tetraploids (i.e., triploid-block, Marks 1966 ). In instances where there is a triploid-block but higher level ploidies in the complex exist, gene flow across ploidies can occur between other intermediates (e.g., pentaploids, Peskoller et al 2021 ; Sutherland and Galloway 2021 ). Despite strong evidence of gene flow across ploidies in some animals ( Bogart et al 2020 ; Novikova et al 2020 ), these processes are even further understudied.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the fitness consequences of hybridizing across ploidies, numerous studies have demonstrated pervasive gene flow between autopolyploids and their diploid relatives when their ranges overlap (Arnold et al 2016; Marburger et al 2019; Monnahan et al 2019; Bogart et al 2020; Novikova et al 2020; Shastry et al 2021; Booker et al 2022). Although hybridization across ploidies during formation is often considered a way for neo-polyploids to overcome the massive population bottleneck during formation (Stebbins 1980), admixture following their establishment should be generally disfavored as mixed-ploidy offspring suffer extensive fitness consequences (Ramsey and Schemske 1998)–though this may be mitigated in higher-level ploidies (Peskoller et al 2021; Sutherland and Galloway 2021). However, hybridization to relieve the deleterious load accumulated through range expansion may help to explain why this phenomenon is so pervasive, and why the evolutionary histories of autopolyploids can be so reticulate (e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The key reproductive isolation mechanism in the formation of triploids is considered to be the triploid block, which operates in different polyploid systems [22,[57][58][59][60]. The triploid block is caused by malfunction of the endosperm as a result of an imbalance between paternally and maternally imprinted genes during the endosperm development, and often leads to seed abortion [61].…”
Section: Sexuality In Cotoneaster Integerrimus Populationsmentioning
confidence: 99%